The Effect of Applying the Discovery Learning Method on Learning to Write Poetry Texts in Grade VIII at SMP N 1 Doloksanggul in the 2023/2024 Academic Year: Pengaruh Penerapan Metode Discovery Learning terhadap Pembelajaran Menulis Teks Puisi di Kelas VIII SMP N 1 Doloksanggul Tahun Pelajaran 2023/2024 - Ipan Sihite (Boraspati Journal: Journal of Bilingualism, Organization, Research, Articles, Studies in Pedagogy, Anthropology, Theory, and Indigenous Cultures, 2025)
This study aims to describe the effect of the application of the discovery learning method on the learning of writing poetry text by students of grade VIII SMP N 1 Doloksanggul in the 2023/2024 learning year. The population of this study were all VIII grade students of SMP N 1 Doloksanggul in the 2023/2024 Learning year which amounted to 240 people. the sample of this study was 30 people who represented the entire population while to determine the sample from the existing population with random sampling techniques (randomized random class). The research method used is the experimental method. to capture data Used to find the effect of certain treatments on learning to write poetry texts as many as 20 objective questions and assign students to write poetry texts. To determine the relationship between the two variables studied, the data analysis technique uses the correlation formula "t" which is called the t-test. The results of data processing obtained the average value of mastery of writing poetry texts of VIII grade students of SMP N 1 Doloksanggul for the control class for the 2023/22024 learning year of 61.5 Including quite good. While the acquisition of the average value of the ability to write poetry by students of class VIII SMP N 1 Doloksanggul for the experimental class for the 2023/2024 learning year of 76.83 includes good criteria. The correlation coefficient of the correlation index (txy) is 0.05 with the interpretation that the contribution of the effect of the application of the discovery learning method to the learning of writing poetry text by class VIII students of SMP N 1 Doloksanggul in the 2023/2024 learning year is a high correlation. Hypothesis testing is done by consulting the price of ttabel with to. The table used is one group preetest-posttest with a significant level of 5% at N = 30 which is 2.639. It turns out that the ttabel obtained is greater than to, namely 2.639 < 4.97. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This is in learning to write poetry by applying the discovery learning method is more effective on the ability to write poetry text by students of class VIII SMP N 1 Doloksanggul in the 2023/2024 learning year.